(3fbV JCSjS GdLgjfIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3aUd bGd GdQGRi HGdbSe GdKGfi ef gPG GdcJGH ai JChjd GdeJTGHgGJ ef GdCNHGQ hGdBjGJ hGdcdGe ajg eQJH Ydi ebOeg haUhd ajbGd ebUhOg HPdc GdBjGJ hGdCNHGQ s
(3BNQgG (B:s
(3GdQO Ydi GdLgejI ajeG JbOe bGd ajg ai hUa bhd GdLge s
(3GdfSNI HgG MhGTs
(3HCfg Jedc HGSe CMeO GdHjWGQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds